Systematic Literature Review: Dimensi Pendidikan Multikultural Indonesia dan Malaysia - Siti Amaliati; R. Nazriyah; Ilham Syifa’; Arifatul Ma’ani (Tadrisuna : Jurnal Pendidikan Islam dan Kajian Keislaman, 2024)
This study aims to synthesize multicultural education models in Malaysia and Indonesia using the systematic literature review (SLR) method. Data was obtained from Google Scholar through Publish or Parish and analyzed using research trends on VOSviewer. The findings show that Indonesia applies an integration model in multicultural education, where multicultural values are integrated in various subjects, rather than as a separate subject. Students can learn and internalize the values of diversity in their daily lives both at school and at home environment. On the other hand, Malaysia uses two models, firstly the separate model, where multicultural education becomes a stand-alone subject, and secondly, the integration model, where multicultural values are integrated into other subjects. This approach helps students in Malaysia understand and appreciate diversity both theoretically and practically in their daily interactions.